(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: A Programmed labour following a protocol teaches the goal of safe motherhood. The present study on programmed labour protocol implemented to shorten the duration of labour, to optimise pain relief during labour, to monitor labour by partograph and to enhance vaginal birth. The prime objective of the study is to evaluate the effect of programmed labour on duration of labour and to assess efficiency of analgesics in reducing severity of labour pain. Materials and methods: Total 100 cases of low risk pregnant women both primi and multipara were included in this study. It was designed to low risk pregnant women with cephalic presentation without evidence of CPD- either with spontaneous onset of labour or waiting for induction of labour at 41+ wks pregnancy. Patient with labour pain allowed to move. Pain relief was done either by pharmacological or nonpharmacological method. Labour was monitored by partograph. Results: The duration were shortened in all stages of labour specially in active phase that was (Mean± SD- 3.08 hr ± 0.83), Significant paint relief in 76% cases (Mean SD of score 2.08 ± 0.62). The rate of vaginal delivery is more in programmed labour which is about 95% in this study. There is also significant reduction of maternal and fetal morbidity and mortality. Conclusion: The programmed labour is simple, easy, cheap and effective method of painless and safe vaginal delivery. Significant reduction of pain by programmed protocol avoid hyperventilation of mother, maintain circulation, thereby increase chance of vaginal delivery. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 72-74